Elaboración de un Plan de Marketing para la Cámara Provincial de Distribuidores de Derivados de Petróleo de la Ciudad de Loja - García Preciado, Claudia Karina (2016)
Currently the Marketing constitutes a vital tool to understand the behavior of markets and consumers. This is the marketing tool and let me raise some alternatives to address the problems and threats, and make better use of the strengths and opportunities that arise within a company. This thesis is focused on the diagnosis, analysis and proposed implementation of strategic plans for the Provincial House Distributors of Oil City Loja, abbreviated CAMDDEPE Loja , to be known at both locally and nationally and its various service stations which unionizes this company. To carry out this study as a first step, a literature review where he unveiled what the background of the Provincial House of Distributors of Oil City Loja (CAMDDEPE Loja ) , a conceptual framework where concepts discussed are performed , marketing structure , and methods were used to conduct a thorough analysis of the company under study. Materials and methods allowed me to move forward with the research topic detailing step by step preparation of this work and likewise through the art of the survey and interview results obtained allowed us to achieve the objectives. Subsequently, a diagnosis which could be identified was held that the Provincial Chamber of Oil Dealers city of Loja. (CAMDDEPE Loja ) , do not have a business philosophy administrative or organizational structure to enable it to meet the mission, vision and corporate values , and different functions to be performed by each of the directors of House. It also became known that CAMDDEPE Loja , do not perform an advertising plan through the media like radio and television , which only carried advertising in the press and rarely Internet , nor there is a virtual platform where you can know the different activities of the company . Promotions are not frequently performed in the House and usually held every owner or hence their trading, as performed any strategic alliances with leading watchdogs ignorance of the duties and rights of each owner of the affiliate stations CAMDDEPE to Loja . An important factor to attract customers is ongoing training that takes CAMDDEPE Loja, to deliver an efficient service through each station employees , whose guidance and training constantly performs in the human relations , customer service , etc. , other aspect to consider is to conduct a SWOT analysis and Porter Matrix that let me access the CAMDDEPE to know their strengths and their weaknesses and threats and opportunities. Resulting in the lack of a business philosophy , Organizational Structure Administrative and Marketing Plans to present to the House and dedicated functions , also with the result that there is no knowledge that is dedicated to the CAMDDEPE in Loja media such as radio , television and website . As often there are no promotions or partnerships that will allow the CAMDDEPE be known. After meeting the diagnostic results of the company six strategic objectives to strengthen viable detailing the Provincial Chamber of Oil Dealers city of Loja ( Loja CAMDDEPE ) solutions was raised. The objectives dealt with the use of an effective and massive advertising campaign to publicize about the company. Finally came to the conclusion and recommend the most feasible for Provincial House Distributors of Oil city of Loja ( CAMDDEPE Loja ) , and it is in the ability to know the different services offered to the owners and staff of the eleven ski Loja service for the best development of their activities.